2020
DOI: 10.3390/s20102751
|View full text |Cite
|
Sign up to set email alerts
|

Performance Optimization of FD-SOI Hall Sensors Via 3D TCAD Simulations

Abstract: This work investigates the behavior of fully depleted silicon-on-insulator (FD-SOI) Hall sensors with an emphasis on their physical parameters, namely the aspect ratio, doping concentration, and thicknesses. Via 3D-technology computer aided design (TCAD) simulations with a galvanomagnetic transport model, the performances of the Hall voltage, sensitivity, efficiency, offset voltage, and temperature characteristics are evaluated. The optimal structure of the sensor in the simulation has a sensitivity of 86.5 mV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This appendix briefly summarizes the previous work of [8] and focuses on the selection of the optimal sensor structure. Compared with the bulk structure, the characteristics of the FD-SOI Hall sensors (such as sensitivity and efficiency) are improved because of its thin thickness and low doping concentration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This appendix briefly summarizes the previous work of [8] and focuses on the selection of the optimal sensor structure. Compared with the bulk structure, the characteristics of the FD-SOI Hall sensors (such as sensitivity and efficiency) are improved because of its thin thickness and low doping concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the conventional bulk Si CMOS (complementary metal-oxide-semiconductor) for Hall sensor manufacturing, the choice of fully-depleted silicon-on-insulator (FD-SOI) technology brings several important advantages. The FD-SOI structure not only has the advantages of less noise generation, lower biasing voltage, and higher integration density [5][6][7], but it has also been confirmed that-compared with the bulk structure-the characteristics of the sensors (such as sensitivity and efficiency) are improved because of its thin thickness and low doping concentration [8].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Figure 2 presents a schematic illustration of the sensor proposed in the present study consisting of a 4-inch silicon wafer, a silicon dioxide insulating layer, metal leads, and a cross-shaped phosphide-doped detection zone [ 25 , 26 , 27 ] For comparison purposes, four devices are fabricated, in which the cross-shaped detection zones have the same aspect ratio (L/W = 2.625), but different sizes, namely S, M, L, and XL. In the proposed devices, the analog signals are amplified by a large-current operational amplifier (AD620) and then supplied to an analog-to-digital converter (MEGA2560).…”
Section: Principle and Designmentioning
confidence: 99%